(untitled) (Journal of International Studies, 2020)
China’s interest and influence in Central Asia has increased since the end of the Cold War. This has been made evident by an increase in energy deals, active participation of the Shanghai Cooperation Organization (SCQ), bilateral ties and military exercises with the Central Asian republics. China is showing its intention of expanding its influence in Central Asia through the SCO. However, since the September 11 attacks, drastic changes have taken place in Central Asia. The US military presence in Central Asia poses a geo-political challenge to China.